Ghrelin, paraoxonase and arylesterase levels in depressive patients before and after citalopram treatment - Barim, Abdullah Onder; Aydin, Suleyman; Colak, Ramis; Dag, Ersel; Deniz, Omer; Sahin, Ibrahim (Pergamon-Elsevier Science Ltd, 2009)
Objectives: The purpose of this study was to examine alterations in lipid profiles and in the serum concentrations of acylated and desacylated ghrelin, paraoxonase and arylesterase in psychiatric patients before and after treatment with 40 mg citalopram daily for 3 months. Design and methods: Samples were collected from 22 healthy controls and 24 psychiatric patients before and after citalopram treatment. Blood levels of acylated and desacylated ghrelin were measured by radioimmunoassay. Paraoxonase and arylesterase activities were determined spectrophotometrically. Lipid parameters were measured on the OLYMPUS-AU400. Results: It was found that the levels of acylated, desacylated ghrelin, paraoxonase arylesterase, total cholesterol and triglyceride were lower in depressive patients before citalopram treatment than in the control group. Those parameters were not restored after citalopram treatment except for the arylesterase level. Conclusion: Decreased PON1 and ghrelin levels as well as fluctuations in lipid profiles may be involved in the etiology of depressive disorders. (c) 2009 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Ghrelin; Paraoxonase; Arylesterase; Major depression